Land Use Changing Pattern And Challenges For Agricultural Land: A Study On Rajshahi District - Islam, Md Rahedul; Hassan, Md Zahidul (Journal of Life and Earth Science, 2012)
Due to alterations in physiographic and social-economic conditions, climatic changes, adaptation and population growth, the land use pattern of Bangladesh is changing very rapidly. Bangladesh is a small country but it bears a huge population, resulting in a very high density of population and very high intensity of land and resource use. Per capita land is estimated to be only about 0.0526 ha. Two significantly prominent phenomena driving country’s overall scenario of economic development and environment imbalance include: (a) the high growth rate of population engulfing precious land for settlement and (b) scarcity of land for ever increasing demand of food. As a result, the land use pattern of the country is changing at a great momentum. Every year the country is losing 1% arable land due to the population growth and its infrastructure development. This study was conducted on Rajshahi District where the major focus was to see the land use pattern of the area, trend in the change of land uses, and in particular, challenges for the agricultural land. For analyses remotely sensed data (Landsat MSS-1977, TM-1990 and TM- 2010) and GIS techniques were used and secondary data were collected from SPARRSO, published and unpublished data regarding crop, population and other ambient information from mostly government sources. Results show that the land use pattern of Rajshahi District is changing, especially the agricultural land is decreasing in an alarming rate and now it is become more and more vulnerable. The agricultural land of the study area is losing 0.46% per year and the area under infrastructure use is increasing 5.86% per year. If this rate continues, the agricultural land will be totally eliminated within the next 217 years. DOI: http://dx.doi.org/10.3329/jles.v6i0.9724 JLES 2011 6: 69-74